STUDY ON THE EFFECT OF BIOCIDE ON MORPHOLOGY AND STRUCTURE OF PAECILOMYCES SP. BY USING TEM AND SEM - Sri Kadarwati; Evita H. Legowo (Testing Center for Oil and Gas LEMIGAS, 2003)
Fungi is one of the types of microbe that can grow in avtur and can give a serious effect, causing fatal accident due to fuel system clogging.